The role of pediatric nursing in the provision of quality care in humanitarian settings: a qualitative study in Tonkolili District, Sierra Leone - Gilday, Josie; Chantler, Tracey; Gray, Nell; Treacy-Wong, Vicky; Yillia, John; Pascal Gbla, Abdul; Howard, Natasha; Stringer, Beverly (International Journal of Nursing Research, 2023)
Purpose: Evaluate nurses' and caretakers' perspectives of quality care, barriers to its delivery, and its study in a humanitarian setting. Methods: A qualitative study using semi-structured interviews and direct observation was conducted in the pediatric department of Magburaka Hospital, Tonkolili district, Sierra Leone. Interviews were recorded, transcribed, and inductive coding was used to identify prevalent themes. The observation was used to compare and elaborate on interview findings. Results: Three themes emerged holistic care; the nursing community; and organization and systems of care. For caretakers, holistic care related to their child‟s survival, with quality care described as the availability of free medication, provision for basic needs (food, water, shelter, sanitation), hospital cleanliness, and psychosocial support. For nurses, this involved medication administration, cleanliness, and carrying out nursing tasks (e.g., taking vital signs). Observation revealed caretakers, without nursing involvement, performed the majority of “activities of daily living” (e.g., bathing, toileting). The nursing community describes nursing employment types, attitudes, and how a lack of teamwork impacted quality nursing care. The third theme outlines the importance of organization and systems of care, in which training and a good salary were perceived as prerequisites for quality nursing care, whilst a lack of resources and inadequate operational systems were barriers. Conclusion: Caretakers play an integral role in the delivery of quality care. This and important quality care components outlined by nurses and caretakers identified a patient and family-centered approach could contribute to improving quality nursing care in humanitarian settings.